THE INFLUENCE OF FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT BEHAVIOR WITH LOCUS OF CONTROL AS AN INTERVENING VARIABLE AT KA.CAB PT. SAMUDERA LAUTAN LUAS MEDAN - Iqbaal Fauzi Pakpahan; Hendra Raza; Naz’aina; Darmawati; Ghazali Syamni; Jummaini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The Influence of Financial Knowledge and Financial Attitude on Financial Management Behavior with Locus of Control as an Intervening Variable at Ka.Cab Pt. Ocean Wide Ocean Medan. This research is quantitative research. In this research, the population is all employees of PT. Samudera Lautan Luas, totaling 105 employees. According to Sugiyono, (2016) the saturated sample determination method or total sampling is a sample determination technique when all members of the population are used as samples. So all members of the population were used as research samples, therefore the researcher took 105 samples. With the results, Financial knowledge has a positive and insignificant effect on Financial Management Behavior, Financial Knowledge has a significant positive effect on locus of control, Financial Attitude has a positive and not significant effect on financial management behavior, Financial attitude has a significant positive effect on Locus of Control, Locus of control has a significant positive effect towards financial management behavior, Locus of control is not able to mediate financial knowledge towards financial management behavior, and Locus of control is able to mediate financial attitude towards financial management behavior.